Maternal Psychological Well-being of School Students in Relation to Education, Family Type, Income, and Working Status (Jagannath University Journal of Science, 2025)
The present study attempted an empirical investigation to explore the maternal psychological well-being of school students in relation to education, family types, income, and working status. An adapted General Health Questionnaire (GHQ-28), and a Personal Information Form (PIF) were administered on the participants to collect data from 400 participants following multistage random sampling technique. Obtained data were analyzed by applying regression analysis, and four-way ANOVA respectively. The study reported that mothers’ education, family types, income, and working status significantly predict their psychological well-being. Results revealed that there were significant differences in mothers’ psychological well-being in terms of education, family types, income, and working status. Furthermore, this study's findings revealed at several interaction effects. As an instance, results indicated that, the interaction effects between family type and working status of mothers were statistically significant in terms of psychological well-being. Results showed that there are significant differences between working mother with nuclear families where working mothers expressed better levels of psychological well-being than the housewife mothers. The findings also showed a substantial difference in psychological well-being between working mothers and housewife mothers with joint families, where working mothers expressing higher levels of psychological well-being than housewife mothers. In light of theory and empirical evidence from previous studies, the findings' implications have been discussed.Jagannath University Journal of Science, Volume 11, Number 2, Dec. 2024, pp. 126−139